"C'est comme ça que cela pourrait recommencer" : L'épineuse question foncière au Burundi. Issue 1 (2nd January 2017) - Wittig, Katrin
Abstract: In recent years, research on land conflicts in war-affected countries has seen a significant increase in the literature on conflict resolution. Land grabbing coupled with the return and repatriation of thousands of refugees and internally displaced persons (IDPs) after the end of civil wars constitute major challenges for peace and reconciliation in many African countries. Drawing on a case study of Burundi, one of Africa's most densely populated countries, this article analyses the complex issues related to land conflicts. Burundi is currently facing thousands of land disputes following the return of refugees and IDPs stemming from the different politico-ethnic crises that this Great Lakes country has endured since independence. The current instrumentalization of the land issue by political entrepreneurs highlights the risks for the fragile peace and reconciliation process that Burundi has known in recent years if the land conflicts are not addressed in a sensitive and equitable manner.